Secondary flow characteristics and their relationship with thermal performance inside the absorber under non-uniform heat flux - Meihong Ye; Weili Gu; Yifan Hou; Xin Xiang; Jiayong Liu (Discover Applied Sciences)
Abstract Under the focusing characteristics of parabolic trough solar collectors, enhancing secondary flow intensity and shifting the secondary flow vortex center towards the bottom of the absorber can extend the lifespan of the absorber and improve thermal performance. This study combines the Monte Carlo Ray Tracing method (MCRT) and the Finite Volume Method (FVM) to investigate the fluid flow and heat transfer characteristics inside the absorber under non-uniform thermal boundary conditions. The effects of inlet flow rate (V in), inlet temperature (T in), and protrusion structures on the secondary flow vortex position are examined. Through numerical analysis, secondary flow intensity (Se), heat transfer coefficient (h), Nusselt number (Nu), and friction factor (f) are calculated. The results show that increasing the Tin significantly enhances secondary flow intensity, thereby improving heat transfer within the absorber. Specifically, when T in increases from 400.15 to 600.15 K, Se increases by a factor of 7.87, while h increases by 98.96%. Increasing the V in shifts the secondary flow vortex downward, enhancing heat transfer at the bottom of the absorber. For example, when V in increases from 100 to 200 L min−1, Se remains largely unchanged, while h increases by 44.68%. Compared to semi-cylindrical protrusions, tetrahedral protrusions are more effective at suppressing the upward shift of the secondary flow vortex, reducing velocity losses caused by fluid-wall interaction, and achieving better heat transfer enhancement. Under conditions of T in = 500.15 K and V in = 100 L min−1, the Nu increases by 14.6% for tetrahedral protrusions and 7.3% for semi-cylindrical protrusions, while the f increases by 12.3% and 10.9%, respectively, compared to the smooth absorber.